2008
DOI: 10.3748/wjg.14.3855
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Helicobacter pylori in surgical practice: A randomised trial of triple versus quadruple therapy in a rural district general hospital

Abstract: AIM:To compare a lansoprazole-based triple versus quadruple therapy for Helicobacter pylori (H pylori) eradication with emphasis on side effect profile, patient compliance and eradication rate at a rural district general hospital in Wales, United Kingdom. C urea breath test 2 mo after treatment. RESULTS: Seven patients were withdrawn after randomisation. Fifty patients were assigned to LAC group and 44 to LMBT group. The intention-to-treat cure rates were 92% and 91%, whereas the perprotocol cure rates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
(33 reference statements)
2
7
0
3
Order By: Relevance
“…Sin embargo, en otros países, como Brasil y Reino Unido, las tasas de erradicación fueron superiores 19,51 , siendo estos resultados similares a los obtenidos en países con bajas tasas de resistencia a claritromicina (menor del 15 al 20%). Adicionalmente, con terapias mayores a 7 días de duración no se encontró mayor eficacia de erradicación, como en los casos de Estados Unidos, Colombia y Chile 24,41,42 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Sin embargo, en otros países, como Brasil y Reino Unido, las tasas de erradicación fueron superiores 19,51 , siendo estos resultados similares a los obtenidos en países con bajas tasas de resistencia a claritromicina (menor del 15 al 20%). Adicionalmente, con terapias mayores a 7 días de duración no se encontró mayor eficacia de erradicación, como en los casos de Estados Unidos, Colombia y Chile 24,41,42 .…”
Section: Discussionunclassified
“…Las tasas de erradicación en análisis por ITT de la triple terapia estándar versus la cuádruple terapia con bismuto de 7 días de duración en el Reino Unido fueron del 92 y del 91%, respectivamente, y en Estados Unidos, con 10 días de duración por ITT, del 83.2 y del 87.7 19,20 . Adicionalmente, en Grecia, con 10 días de duración, el porcentaje de erradicación por ITT para la triple terapia fue del 78%, y para la terapia cuádruple, del 65% 21 .…”
Section: Ensayos Clínicos Aleatorizadosunclassified
“…The sensitivity analysis showed that both the eradication rate and the inci- T a b l e 1 . Ch a r a c t e r i s t i c s o f I n c l u d e d S t u d i e s ( 2 1 , 2 7 , 2 9 , 3 5 (36)(37)(38). Related to these drawbacks, more effective, simpler, and better tolerated regimens Nista (27) Bago (21) Liu (29) Kilic (35) 48.9%…”
Section: Resultsmentioning
confidence: 99%
“…After detailed review of selected articles, 12 RCTs [8,9,10,11,12,13,14,15,16,17,18,19] with 2,753 patients fulfilled the inclusion criteria of the meta-analysis (fig. 1).…”
Section: Resultsmentioning
confidence: 99%